Do office workers adjust their chairs? End-user knowledge, use and barriers to chair adjustment. (May 2019) - Underwood, Diana; Sims, Ruth
Abstract: A quantitative field study measured end-user availability, knowledge and use levels of adjustable office chair functions in Korea-based office workers, together with their perceived barriers towards making adjustments. Fifty-one English-speaking workers were interviewed and surveyed in a related design. Results showed that of the number of adjustable functions available on their office chair ( M = 5.39, SD = 2.3), participants knew fewer than half of them ( M = 2.51, SD = 1.52) and used even less ( M = 1.86, SD = 1.21). Fifty-three percent of participants knew two or less and 73% had used only two or less. Ten percent had used none. Results suggested physical needs (such as increased comfort or postural change) were a strong driver for previous chair adjustment behaviour. Perceived cognitive barriers played a more significant role in limiting chair adjustment knowledge and use than physical or organizational barriers. Highly adjustable office chairs have the possibility of satisfying the adjustment needs of most end-users. However, adjustable chair functions need to be both available and known in order to be used. Highlights: Users knew and used fewer than half of their office chair's adjustable functions. Physical needs were a strong driver for previous chair adjustment behavior. Perceived cognitive barriers limited chair adjustable function knowledge and use. Chair adjustable functions need to be available and known in order to be used.